STABILITY OF INTEGRO DIFFERENTIAL EQUATIONS WITH IMPULSES - Sariyasa . (IndoMS, 2007)
Sufficient conditions have been derived for the asymptotic stability of the trivial solutions of a class of linear integrodifferential equations under impulsive per-turbations. The sufficient conditions are formulated in terms of the parameters of the equations such that in the absence of the impulsive effects, these conditions are reduced to those of the non-impulsive equations. doi: http://dx.doi.org/10.22342/jims.13.1.71.17-26